Developing Listening Textbook for Eight Grader of Junior High School Based On Contextual Teaching and Learning - Sholah, Hanif Maulaniam (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2023)
The need of listening textbook is not balanced with the available listening book on market, bookstore and education ministry department. This research produces a listening textbook which is based on researcher need analysis. The result of preliminary study conducted in 10 Junior High Schools in Malang shows that the need of listening textbook is considered important. The available textbook is not supported by material in form of audio and video. Teacher feels difficult to find any sources to teach listening. By conducting this research, it is expected to help English teacher to teach listening well. The result of this research is a product in form of textbook that can be used by English teacher to teach Listening skill. The design of this research is Research and Development that is well known as R and D. Research and Development (R&D) is a process or steps to develop or to revise a product. The product is not only in form of software program like program in computer to analyze the data, but also in form of textbook, module, some equipment in laboratory, library, management and etc. In this research, the product is in form of a textbook. By having this product, the students will be able to learn listening better because this product is completed with some interesting pictures, good audio and appropriate material that will be validated by some experts. For sure, since the process of making this product is passing many steps, the researcher believe that this product is good for students. It supplies the need of Eight grade students of Junior High School. Each chapter of the book presents some pictures which the students have already known or the pictures easily found by the students in their real life or environment. It also presents some exercises, like translating and matching words to test the students’ understanding about the lesson in each chapter. Covering speaking aspect, the textbook delivers conversation to train the students’ speaking skill.